0951 NAP-RELATED VARIATION IN SLEEP PROPENSITY AND REM TENDENCY ON THE MSLT: IMPLICATIONS FOR PEDIATRICS - Cairns, A; Bogan, R (Sleep (New York, N.Y.), 2017)
Abstract Introduction: It is often assumed that patients are increasingly unlikely to fall asleep (and have REM) toward the latter naps of a clinical MSLT. However very little data is available on this subject, especially as it relates to pediatrics. This study aims to explore age*nap-related changes in the likelihood of sleep and REM over the course of 5 consecutive naps in a large sample of clinical MSLTs. Methods: Data were extracted from SleepMed’s repository of deidentified PSG and 5 nap MSLTs. Sleep onset was defined as initial sleep latency (ISL) and studies were executed as per AASM guidelines. Studies were excluded if <360 minutes of sleep time was recorded on the previous night’s PSG or if the patient worked shift/nights. Nap-related variability in sleep/REM was assessed with McNemar tests and mixed model ANOVA. Results: The final sample was 1767 patients with a mean age of 34 years (range 4–89 years; 70% Caucasian; 63% female). The likelihood of sleep (y/n) was highest for nap1 and nap2 (93% and 91%; p=.50) and decreased thereafter (nap3=88%, nap4=85%, and nap5=75%; all p’s<.001). Likewise, sleep latency increased over the course of the MSLT (from 7 to 10 min; p<.001). REM tendency (y/n) was highest for nap2 (22%) and lowest for nap4 (14%). Children <12 years (n=159) were generally less likely to fall asleep and had longer MSLs than those older (MSL=11.6 vs. 7.5 min; p<.001) and were particularly unlikely to fall asleep as the MSLT progressed (from 82% at nap1 to 54% at nap5). Similar to those older, children had the lowest rate of REM on the 4th nap (15%) but the highest rate on the 1st nap (30%). Conclusion: These data confirm the hypothesis that sleep becomes more unlikely as the MSLT progresses, at least partially attributable to increasing circadian drive for alertness in combination with dissipated sleep pressure. The finding that REM tendency is non-linearly distributed highlights the importance of a 5-nap MSLT when only 1 REM period is observed in the first 4 naps. Lastly, these data highlight the need for age-appropriated MSLT practice parameters. Support (If Any):